An assessment of the impact of host polymorphisms on Plasmodium falciparum vargene expression patterns among Kenyan children - Warimwe, G; Fegan, G; Kiragu, E; Musyoki, J; Macharia, A; Marsh, K; Williams, T; Bull, P (BioMed Central, 2014)
Background: Host genotype accounts for a component of the variability in susceptibility to childhood Plasmodium falciparum malaria. However, despite numerous examples of host polymorphisms associated with tolerance or resistance to infection, direct evidence for an impact of host genetic polymorphisms on the in vivo parasite population is difficult to obtain. Parasite molecules whose expression is most likely to be associated with such adaptation are those that are directly involved in the host-parasite interaction. A prime candidate is the family of parasite var gene-encoded molecules on P. falciparum-infected erythrocytes, PfEMP1, which binds various host molecules and facilitates parasite sequestration in host tissues to avoid clearance by the spleen. Methods: To assess the impact of host genotype on the infecting parasite population we used a published parasite var gene sequence dataset to compare var gene expression patterns between parasites from children with polymorphisms in molecules thought to interact with or modulate display of PfEMP1 on the infected erythrocyte surface: ABO blood group, haemoglobin S, alpha-thalassaemia, the T188G polymorphism of CD36 and the K29M polymorphism of ICAM1. Results: Expression levels of ‘group A-like’ var genes, which encode a specific group of PfEMP1 variants previously associated with low host immunity and severe malaria, showed signs of elevation among children of blood group AB. No other host factor tested showed evidence for an association with var expression. Conclusions: Our preliminary findings suggest that host ABO blood group may have a measurable impact on the infecting parasite population. This needs to be verified in larger studies.